THE FORMATION OF SOYBEAN YIELD INFLUENCED BY INOCULATION AND FEEDING - Новицька, Н. В.; Джемесюк, О. В. (Scientific Progress & Innovations, 2017)
The article deals with the influence of inoculation and foliar feeding with multi-chelate complex and colloidal solution of metal nanoparticles on the yield performance of ultra and early ripening varieties of soybean. It had been found, that pre-inoculation of seeds with «HayKot Super» inoculant provides additional 2–4 t/ha yield allowances. Carrying out foliar feeding with chelated micro-fertilizers increases soybean yield performance by 10–15 %. Use of nano-metals for spraying soy at the stage of budding as a solution (240 mg/l) while mineral fertilizers applying at a rate of N30P60K60 increases the yield performance of a crop at 2,8 t/ha. The maximum yield performance indicators of soybean were obtained by combining the seeds inoculation, mineral fertilizers application at a rate of N30P60K60 and use of complex fertilizers «Rostock bean» (2 l/ha) for the foliar feeding.